2014
DOI: 10.1002/2014gl059478
|View full text |Cite
|
Sign up to set email alerts
|

Geologic structure generated by large‐impact basin formation observed at the South Pole‐Aitken basin on the Moon

Abstract: The South Pole-Aitken (SPA) basin is the largest clearly recognized basin on the lunar surface.Determining the composition and structure of the SPA basin interior provides critical constraints on the deep crustal and/or mantle composition of the Moon and improves our understanding of large-basin-forming impact processes. Here we present a new mineralogical map of the SPA basin interior, based on high-spatial-resolution reflectance spectra using the SELENE (Kaguya) multiband imager, which is combined with topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 36 publications
7
68
0
Order By: Relevance
“…The target area in this study is denoted as the black square in Figure . We selected this area because it has been suggested that the impact melt of the SPA generated an impact melt sheet in this region (central depression (CD); 315 and 291 km in radius and 53.7°S, 162.6°W) [ Ohtake et al , ]. We generated a reflectance map and a color composite image of several rock types derived by MI spectra to classify and identify the mineralogy and the distribution of surface lithologies within the target area (Figures a and b).…”
Section: Classification and Distribution Of Each Lithologymentioning
confidence: 99%
See 1 more Smart Citation
“…The target area in this study is denoted as the black square in Figure . We selected this area because it has been suggested that the impact melt of the SPA generated an impact melt sheet in this region (central depression (CD); 315 and 291 km in radius and 53.7°S, 162.6°W) [ Ohtake et al , ]. We generated a reflectance map and a color composite image of several rock types derived by MI spectra to classify and identify the mineralogy and the distribution of surface lithologies within the target area (Figures a and b).…”
Section: Classification and Distribution Of Each Lithologymentioning
confidence: 99%
“…We used SELENE (Kaguya) Multiband Imager (MI) data of higher spatial resolution and wider wavelength than previous data to observe the mineralogical and chemical distribution within the SPA in detail. Our previous study, which observed within the SPA basin, suggested the location where the SPA impact melt was pooled [ Ohtake et al , ] in the center of the SPA (central depression (CD)) based on not only elevation but also surface roughness and composition. Therefore, in this study, we focused on the area within and surrounding the CD and investigated the detailed lithology of the area.…”
Section: Introductionmentioning
confidence: 99%
“…Its geology provides insights into the composition of the lower crust and upper mantle, the impact flux in early lunar history, the nature and evolution of basin‐scale impact melt deposits, and the nature of large impact basins and their formation and modification processes (Garrick‐Bethell & Zuber, ; Head et al, ; Moriarty & Pieters, ; Potter et al, ; Spudis et al, ; Vaughan & Head, ). The SPA basin has been studied with spectral observations (e.g., Ohtake et al, ; Pieters et al, ) and recently been subdivided into four distinct compositional zones based on Moon Mineralogy Mapper (M 3 ) data (Moriarty & Pieters, ): (1) a central ~700‐km‐wide SPA compositional anomaly (SPACA), which exhibits a strong Ca‐pyroxene signature, which is different from typical mare basalts; (2) a Mg‐Pyroxene Annulus, which is characterized by Mg‐rich pyroxenes; (3) a Heterogeneous Annulus, which exhibits mixing of localized pyroxene‐rich units and feldspathic materials; and (4) the SPA Exterior, which is mafic‐free and dominated by feldspathic materials. Pyroxene compositions in both the Heterogeneous Annulus and Mg‐Pyroxene Annulus are similar.…”
Section: Introductionmentioning
confidence: 99%
“…Schrödinger basin is a complex impact structure centred at 75°S, 132.5°E—near the southwestern rim of the Moon's oldest and largest impact basin, South Pole-Aitken (SPA), where a few kilometres of SPA ejecta3, dominated by a mantle component456, covered farside crust. Schrödinger is believed to be an early Imbrian-aged impact feature (that is, ca .…”
mentioning
confidence: 99%